Break your own rules : how to change the patterns of thinking that block women's paths to power - Flynn, Jill, 1945-; Heath, Kathryn, 1949-; Holt, Mary Davis, 1950- (San Francisco, CA : Jossey-Bass, 2011)
'How women can make it to the top by adopting the new rules of leadershipWomen hold just 11 percent of the most senior-level leadership positions in U.S. Corporations--a number that hasn't changed in over 30 years. How can women break through? Break Your Own Rules distills the six faulty assumptions (or'rules') most women follow that get in the way--then delivers the correlating new rules that promise to clear that path. For example, the old rule of'Focus on Others' must be replaced by'Take Center Stage,''Hard Work Will Get You There' must yield to'Be Politically Savvy.''Play It Safe' must give way to'Play to Win.''Ask Permission' must be replaced by'Proceed Until Apprehended.' Features the results of over 1,700 interviews with executives in Fortune 1000 companies, as well as the authors' new research and ongoing work with over 5,000 professional women Showcases previously-untold stories from high profile women including Ann Moore (CEO, Time Inc.), Susan Ivey (CEO, Reynolds American), Cathy Bessant (Global Executive for Technology and Operations for Bank of America), Lynn Ford (CEO, ING Solutions), and more Reveals what it really takes for any woman to succeed at the highest levels Foreword by Sharon Allen, Chairman of Deloitte This hands-on guide is for women who are ready to transform their assumptions and join the senior ranks of American business'--Provided by publisher.
Our vision -- Break your own rules -- Take center stage -- Proceed until apprehended -- Project personal power -- Be politically savvy -- Play to win -- It's both-and -- Stand together and close ranks -- Reading list for women leaders.
Includes bibliographical references and index.
Keywords: Women executives -- Psychology; Businesswomen -- Psychology; Assertiveness in women; Women -- Promotions; Success in business